Analytical Determination of Electric Voltage for Pressure-driven Flow Through Complex Microchannels (Journal of Fiber Bioengineering and Informatics, 2013)
An analytical determination of electric voltage generated by the pressure-driven flow through complexmicrochannels was analyzed based on the fractal theory. The pressure-driven flow through a complexmicrochannel with consideration of electrokinetic phenomena is described by the momentum and Poisson-Boltzmann (P-B) equations. The solution of induced electric field strength and electric voltage acrosscomplex microchannels are obtained using the fractal theory and technique, which are the function ofdimensionless electroosmotic radius and the porosity. The results obtained show that the analyticalresults are agreed well with the experimental data.
Keywords: Fractal Theory; Electrical Double Layer; Electric Voltage; Porosity